The Role of Women Fish Besek Craftsmen in Improving the Family Economy in Sumbersewu Village, Muncar District, Banyuwangi Regency - Asfarina Hidayah (Airlangga University, 2021)
The purpose of this study was to determine the role of fish besek craftsmen in improving the family economy and to determine the success rate of fish besek craftsmen in improving the family economy. This research is a qualitative descriptive study that emphasizes the role and success rate of besek fish craftsmen in improving the family economy in Sumbersewu Village, Muncar District, Banyuwangi Regency. Data collection techniques in this study were interviews, observation, and documentation. Data analysis techniques used in this research are data collection, data reduction, data presentation and finally drawing conclusions. The results showed that the role of women fish craftsmen in improving the family economy was the role of earning a living (community) and the role of housewives (domestic), while the success rate of women fish meat craftsmen in improving the family economy was around 32%-42% which on average its contribution to family income is 37%. The results of this study indicate that the role of besek fish craftsmen is quite large in improving the family economy.Keywords: fish basket, women, craftsmen, income